PENGARUH MEKANISME CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Survei Pada Perusahaan Manufaktur yang terdaftar di BEI ) - Animah, Animah; Effendy, Lukman; Thahir, Alamsyah M.; Widiastuty, Erna (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
The purpose of this research is to examine the effect of corporate governance mechanisms,  firm size of financial performance. The Population of this research is the company manufacturing  in BEI. The sampling technique used is purposive sampling. The analytical tool used is using partial least  square program. The independent variables in this research are corporate governance mechanism,  firm size  while the dependent variable is the performance of the financial. The result of the research shows that firm size  influence to financial performance, while other variables such as corporate governance mechanisms have no effect negative  to financial performance.